Comparative evaluation of ageing effects on the properties of regular and highly polymer modified asphalt binders. (4th October 2021) - Rivera, Carlos; Caro, Silvia; Arámbula-Mercado, Edith; Sánchez, Diana B.; Karki, Pravat
Highlights: We experimentally assessed a HiMA binder and a regular polymer modified binder (PMA). Rheological, chemical and thermodynamic properties were quantified at various ageing states. Modulus and surface free energy of mastics with both binders were also evaluated. The modulus of the HiMA binders and mastics were smaller than those of the PMA. HiMA materials outperformed in terms of fatigue, rutting and adhesion quality. Abstract: The use of polymer modified asphalt is steadily growing due to the increasing loading demands in asphalt pavements. Although common polymer modification doses range between 2.5 and 3.5% by weight of asphalt binder, higher dosages are being increasingly used to enhance the performance and durability of asphalt mixtures. These higher doses range between 7 and 8% by weight of asphalt, and the resulting binders are denoted as highly or heavily modified asphalts (HiMA or HP). The objective of this work is to characterize and compare different fundamental material properties and the expected mechanical performance of a regular polymer modified and a HiMA asphalt at the binder and mastic levels, under different ageing conditions. The results confirm an enhanced expected long-term mechanical performance of the HiMA asphalt in road projects as compared to conventional polymer modified binders.